2016
DOI: 10.1039/c5ra25517a
|View full text |Cite
|
Sign up to set email alerts
|

One-step preparation of graphene oxide–poly(3,4 ethylenedioxythiophene) composite films for nonvolatile rewritable memory devices

Abstract: A nonvolatile rewritable memory composite film consisting of PEDOT and GO has been prepared by using GO-initiated photopolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The bandgap of GO was known to be variable and affected by a number of factors 54 , 55 . In order to determine the lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energy levels of GO in our device, the UV-vis absorption spectrum and cyclic voltammetry ( C - V ) sweeps for GO film were measured.…”
Section: Resultsmentioning
confidence: 99%
“…The bandgap of GO was known to be variable and affected by a number of factors 54 , 55 . In order to determine the lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energy levels of GO in our device, the UV-vis absorption spectrum and cyclic voltammetry ( C - V ) sweeps for GO film were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, natural DNA has the Highest Occupied Molecular Orbital (HOMO) and Lowest Unoccupied Molecular Orbital (LUMO) energy levels with around −5.30 and −1.08 eV, respectively . The PEDOT: PSS electrode has a similar HOMO level (−5.2 eV) to that of the DNA, which leads to a lower energy barrier for hole injection. In contrast, the probability of electron injection from the electrode is lower due to the higher energy gap between the LUMO level of the DNA and that of PEDOT:PSS (−3.2 eV).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further insight into the current conduction mechanism of the fabricated Al/TPA-Cz PI/ITO device, the negative part of the switching curve in triplet state was analyzed by logarithmic coordinates as shown in Figure 7(a), according to reported in the literature. 3,29 32 For the memory device of TPA-Cz PI, according to the linear fitting, it was found that the I-V relationship in the ON2 state showed an Ohmic conduction behavior with a slope of 1.0 and the linearity degree of 1.00, which was considered to be the formation of conductive filament, during the region of approximately –3.0 to –0.06 V, as shown in Figure 7(b), following the Ohmic conduction model 3 …”
Section: Resultsmentioning
confidence: 99%